Gamma-aminobutyric acid and glutamic acid levels in the auditory pathway of rats with chronic tinnitus: a direct determination using high resolution point-resolved proton magnetic resonance spectroscopy (1H-MRS) - Brozoski, Thomas J.; Odintsov, Boris (Frontiers in Systems Neuroscience, 2012)
Damage to the auditory system following high-level sound exposure reduces afferent input. Homeostatic mechanisms appear to compensate for the loss. Overcompensation may produce the sensation of sound without an objective physical correlate, i.e., tinnitus. Several potential compensatory neural processes have been identified, such as increased spontaneous activity. The cellular mechanisms enabling such compensatory processes may involve down-regulation of inhibitory neurotransmission mediated by γ-amino butyric acid (GABA), and/or up-regulation of excitatory neurotransmission, mediated by glutamic acid (Glu). Because central processing systems are integrated and well regulated, compensatory changes in one system may produce reactive changes in others. Some or all may be relevant to tinnitus. To examine the roles of GABA and Glu in tinnitus, high-resolution point resolved proton magnetic-resonance spectroscopy (1H-MRS) was used to quantify their levels in the dorsal cochlear nucleus (DCN), inferior colliculus (IC), medial geniculate body( (MGB), and primary auditory cortex (A1) of rats. Chronic tinnitus was produced by a single high-level unilateral exposure to noise, and was measured using a psychophysical procedure sensitive to tinnitus. Decreased GABA levels were evident only in the MGB, with the greatest decrease, relative to unexposed controls, obtained in the contralateral MGB. Small GABA increases may have been present bilaterally in A1 and in the contralateral DCN. Although Glu levels showed considerable variation, Glu was moderately and bilaterally elevated both in the DCN and in A1. In the MGB Glu was increased ipsilaterally but decreased contralaterally. These bidirectional and region-specific alterations in GABA and Glu may reflect large-scale changes in inhibitory and excitatory equilibrium accompanying chronic tinnitus. The present results also suggest that targeting both neurotransmitter systems may be optimal in developing more effective therapeutics.